2021
DOI: 10.4054/demres.2021.44.5
|View full text |Cite
|
Sign up to set email alerts
|

A decade of TFR declines suggests no relationship between development and sub-replacement fertility rebounds

Abstract: BACKGROUNDHuman development is historically associated with fertility declines. However, demographic paradigms disagree about whether that relationship should hold at very high levels of development. Using data through the late 2000s, Billari (2009, 2011) found that very high national levels of the Human Development Index (HDI) were associated with increasing total fertility rates (TFRs), at least at high levels of gender parity. OBJECTIVEThis paper seeks to update that finding and to introduce the Human Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Linkages between economic conditions in a country, or region, and community characteristics have been discussed across demographic (Arpino & Tavares, 2013;Bleha & Ďurček, 2017), sociological (Hank, 2002) and economic (Sato, 2007) studies, but past research has found different effectsmainly depending on the area's level of development and the period analyzed. For medium-or highincome countries, there has been a discussion over a reversal in the fertility trend (Gaddy, 2021;Myrskyla et al, 2009) based on the idea that an area's socioeconomic development is associated with a decline in fertility only up to a certain point, after which the association becomes positive (Day, 2012;Myrskyla et al, 2009). Yet the question remains: What leads to such a reversal in the relationship?…”
Section: Globalization Complexity and Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Linkages between economic conditions in a country, or region, and community characteristics have been discussed across demographic (Arpino & Tavares, 2013;Bleha & Ďurček, 2017), sociological (Hank, 2002) and economic (Sato, 2007) studies, but past research has found different effectsmainly depending on the area's level of development and the period analyzed. For medium-or highincome countries, there has been a discussion over a reversal in the fertility trend (Gaddy, 2021;Myrskyla et al, 2009) based on the idea that an area's socioeconomic development is associated with a decline in fertility only up to a certain point, after which the association becomes positive (Day, 2012;Myrskyla et al, 2009). Yet the question remains: What leads to such a reversal in the relationship?…”
Section: Globalization Complexity and Fertilitymentioning
confidence: 99%
“…Over the second half of the 20th century, one of the relatively most straightforward associations identified regarding fertility was the negative effect of economic development. Since the middle of the last century, much academic effort has been devoted to the study of this effect, as well as to searching for the reasons behind this negative association (Anderson & Kohler, 2015 ; Caldwell, 1976 ; Gaddy, 2021 ; Galor & Weil, 2000 ; Lesthaeghe, 1995 ). Recently, however, this accepted regularity is straining, and renewed attention has been paid to the link between economic development and total fertility (Herzer et al, 2012 ; Hofmann & Hohmeyer, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Speculations in this direction may show a different stage five implying increasing birth rates coexisting with low death rates eventually producing a further sharp increase in total population worldwide. However, this view could support the idea that fertility rates should rise also at very high levels of economic development, which is at odds with the main view of the demographic literature (e.g., Gaddy, 2021) unless considering the catastrophic effects of infectious diseases, with specific regard to the fertility reversal effect of HIV/AIDS in SSA (Kalemli-Ozcan and Turan, 2011; Kalemli-Ozcan, 2012; .…”
Section: 2mentioning
confidence: 94%
“…By considering the expressions in (17), the Jacobian matrix evaluated at a generic stationary state equilibrium (c * , k * , L * ) reads as:…”
Section: The Instantaneous Utility Function At Time T Of the Representative Agent Ismentioning
confidence: 99%
“…[code for this is "countries and states gdp fertility.do"] A lower standard of living is associated with higher birth rates. However, economic crises cause declines in fertility (Currie and Schwandt 2014), and this was especially true around the 2008 recession in the U.S. (Comolli 2017;Schneider 2015) and other high-income countries (Gaddy 2021). The crisis interrupted what had been a mild recovery from falling total fertility rates in highincome countries, leading to a decline from 1.74 in 2008 to 1.57 by 2019 (Figure 2).…”
Section: Review and Contextmentioning
confidence: 99%